PENGARUH KEMIRINGAN POROS BALING-BALING TERHADAP KECEPATAN PERAHU KETINTING - M Nur Habib; Eliza R de Fretes; Sonja T. A. Lekatompessy (ALE Proceeding, 2021)
Ketinting boat in operation using propeller with engine located on deck. This position resulted in the propeller dipping by making a certain angle, in addition the depth of the propeller also overlapped the speed of the ship.This phenomenon is something very important to be examined with the aim of obtaining maximum speed in relation to the angle of tilt of the propeller and the amount of maximum thrust required.The method used is an experimental method in which the model of the ship and propeller are made according to the desired scale, and so conduct testing on the towing tank.The test result obtained is a slope that creates the optimal speed of the ketinting boat is at a slope of 18Â° with a speed of V = 5.05 knots and a maximum thrust of PT = 13.15 kW.